MOTHER’S KNOWLEDGE TOWARDS REVISED IMMUNIZATION SCHEDULE AT RURAL AREA - Astik Ingale, Swati; Vijay More, Mayuri; Shinde, Mahadeo (International Journal of Psychosocial Rehabilitation, 2020)
Mothers are the first care providers of their children. One of the ways to achieve a reduction of under-five mortality is to educate the mothers on matters pertaining to childcare. Immunization is a most cost-effectiveness health interventions known to the mankind Study objectives were to assess the knowledge regarding the revised immunization schedule and find the association between pre-test knowledge scores. Methods: A descriptive study was conducted at a primary health center. Non-probability The purposive sampling technique was used for selecting 30 mothers of children under five. Data was collected with structured questionnaire Data was analyzed by using SPSS software. Result: The maximum number, 18 (60%), of mothers belong to the age group of 18 to 24 years. The majority ofs, 12 (40%), studied up to secondary education; 27 (90%) mothers were housewives; 23 (77%) were Hindu; 18 (60%) belonged to joint families; 13 (44%) of mothers had monthly incomes of Rs 6000 to 10000; and 24 (80%) received information from health professionals like doctors and  It shows that out of 30s, 18 (60%) had inadequate knowledge; the mean knowledge score was 17.4 ± 3.54. The result shows that there was no association found between the knowledge of mothers regarding the revised national immunization schedule program and selective demographic variables. Conclusion: Based on the result of the present study concluded that the knowledge of mothers of children under five regarding the revised national immunization program was at an inadequate level. So there is a need to provide proper information about the revised immunization schedule to the mothers.